Gender Invariance of the Screening Scale for Generalized Anxiety Disorder (EDTAG) - Gonzalez-Betanzos, Fabiola (2015)
The present paper shows how to evaluated invariance using confirmatory factor analysis models for means and covariances (CFA-MACS) for categorical data and models of Item Response Theory (IRT). Invariance analysis in the study of Detection Scale Generalized Anxiety Disorder comparing men and women is exemplified. The scale is widely used in health institutions and by its nature (a brief scale of 12 dichotomous items) any measurement error can have a major impact. Results have shown that the scale has the same configuration, but the item 9 shows differential item functioning, being males more likely to respond affirmatively compared to women in the same trait level. The need for this type of analysis on the scales is discussed.